2012
DOI: 10.1002/ange.201205294
|View full text |Cite
|
Sign up to set email alerts
|

Koordinationschemie an Kohlenstoff: die Patchwork‐Familie bestehend aus (Ph3P)2C, (Ph3P)C(C2H4) und (C2H4)2C

Abstract: Carbodiphosphorane · Cyclopropane · Olefinliganden · Phosphorylide · Spiropentane Einführung und HistorieUngefähr zwei Jahrhunderte lang galt die Koordinationschemie als eine Domäne der Hauptgruppen-und Übergangsmetalle mit einzelnen Metallatomen [wie in Tetracarbonylnickel(0)] oder -ionen [wie in Tetrafluoridoberyllat(II) oder Dicyanidoaurat(I)] als Koodinationsstellen für eine große Vielzahl neutraler oder anionischer Liganden. Typischerweise wurden die Metallzentren als positiv geladene oder anderweitig ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 186 publications
0
4
0
3
Order By: Relevance
“…The syntheses of (BH)(cAAC) 2 9 and the carbodicarbene C(NHC) 2 ,18 which were suggested by our theoretical studies,17, 19 are clear evidence for the usefulness of the donor–acceptor model for predicting molecules that can be reasonably described with dative bonds 20. Contrary to a posteriori depictions of experimental results in terms of Lewis structures, the model makes it possible to understand and to predict experimental findings.…”
Section: Eda‐nocv Calculations Of the Donor–acceptor Complexes (N+)l2mentioning
confidence: 71%
“…The syntheses of (BH)(cAAC) 2 9 and the carbodicarbene C(NHC) 2 ,18 which were suggested by our theoretical studies,17, 19 are clear evidence for the usefulness of the donor–acceptor model for predicting molecules that can be reasonably described with dative bonds 20. Contrary to a posteriori depictions of experimental results in terms of Lewis structures, the model makes it possible to understand and to predict experimental findings.…”
Section: Eda‐nocv Calculations Of the Donor–acceptor Complexes (N+)l2mentioning
confidence: 71%
“…[13,14] However,t he dative fragmentation pattern 1B has also been proposed in analogy to transition-metal complexes. [15] Previous DFT studies have already revealed that often different (also unsymmetrical) structures must be considered to fully describe the electronic distribution in metalated ylides. [16,17] Yet, no influence of the metal ion has been considered to date.…”
Section: Introductionmentioning
confidence: 99%
“…An example of a very well-balanced description can be found in a recently published article by Schmidbaur and Schier. [10] In any case, dative bond arrows should be avoided, when one single conventional representation is entirely sufficient. In the following we will demonstrate this transition.…”
mentioning
confidence: 99%